Substituent Effects on Physical Properties and Catalytic Activities toward Water Oxidation in Mononuclear Ruthenium Complexes. Issue 33 (4th November 2015) - Sato, Yoichi; Takizawa, Shin‐ya; Murata, Shigeru
Abstract: A series of monomeric Ru II complexes [Ru(bda)(pyR)2 ] (H2 bda = 2, 2′‐bipyridine‐6, 6′‐dicarboxylic acid, pyR = pyridine with a substituent R at the 4‐position) were prepared, and the effects of substituent groups on the pyridine ligands of the complexes on catalytic activities toward water oxidation, as well as on photophysical and electrochemical properties, were examined. An increase in the electron‐withdrawing ability of the substituent results in a redshift of the absorption maximum assigned to the transition from the d orbital of Ru to the π* orbitals of the pyridine ligands, and an increase in the oxidation potential of the complex. These results are reasonably explained in terms of the variation of the energy level of molecular orbitals induced by the substituent group, which is supported by density functional theory calculations. The substituent effect on catalytic activity toward photochemical water oxidation using [Ru(bpy)3 ] 2+ (bpy = 2, 2′‐bipyridine) and S2 O8 2– as a sensitizer and a sacrificial electron acceptor, respectively, is essentially analogous to that toward chemical water oxidation using Ce IV as an oxidant in which the complexes with electron‐withdrawing groups exhibit better performance than those with electron‐donating groups. However, the Hammett analysis demonstrates that the catalytic activities of the complexes toward chemical and photochemical water oxidation show no straightforward dependence on the electronic nature of the substituent group, which suggests that a step accelerated by electron‐donating groups also contributes to the overall rate of water oxidation. Abstract : Hammett analysis demonstrates that the catalytic activities of the monomeric Ru II complexes toward chemical () and photochemical (▴) water oxidation show no straightforward dependence on the electronic nature of the substituent groups on the pyridine ligands of the complexes.